Perbandingan Hasil Belajar Biologi Strategi Pembelajaran Aktif Tipe Make A Match dan Card Sort - Nurul Aini; Slamet Santosa; Bowo Sugiharto (Universitas Sebelas Maret, 2014)
The purpose of the research is ascertain the differences result learning achievement in biology on active learning strategies Make a Match and Card Sort Class X SMA Negeri 5 Surakarta academic year 2012/2013. The research method was quasy experiment using quantitative approach. The populations was all students of class X SMA Negeri 5 Surakarta academic year 2012/2013 with 297 students. The sample of this research was established by cluster sampling, so chosen X3 as the experiment 1 class with 29 students and X4 as the experiment 2 with 30 students. Data was collected using multiple choice test, observation sheet, and document. The data were analyzed by t-test. The results of the study showed that Make a Match strategy has 67.37 for the cognitive side, 81.46 the psychomotor side, and 77.58 for the affective side; while Card Sort strategy has 63.42 for the cognitive side, 73.92 for the psychomotor side, and 78.53 for the affective side. Decision take hypothesis with level of significance (α : 0,05). Ho rejected if probability significance less than 0.05 and accepted if more than 0.05. In the cognitive domain showed 0.039 > 0.05, the shows psychomotor domain 0.049 <0.05, and the affective domain, showed 0.69> 0.05. The conclusion of this research were have differences results of biological studies on the cognitive and psychomotor from the application of active learning strategies Make a Match and application of active learning strategies Card Sort Class X students of SMA Negeri 5 Surakarta academic year 2012/2013. Key Words: Active Learning Strategies Make a Match, Active Learning Strategy Card Sort, Learning Achievement in Biology